Sentidos da humanização no processo ensino-aprendizagem da graduação em Medicina - Costa, Alexsandro Nascimento (2015)
This study presents the research carried out through the Professional Master's Program of Health Teaching (MPES) of the Faculty of Medicine of the Federal University of Alagoas, in the years of 2013 and 2014, and financed by FAPEAL, as well as the intervention product to be Developed in the Medicine course of the State University of the Southwest of Bahia - Campus Vitória da Conquista - Bahia. The justifications and personal motivations for the accomplishment of this work were based on the practice in the classroom, in the experience as a nurse militant of the Collective Health and in the observation, as well as in the theoretical investigation, realized on the thematic one. The aim of the research was to study the medical students from UESB - Vitória da Conquista in relation to the humanization of health in undergraduate courses. For its development the qualitative approach was used under the methodological contribution of Discourse Practices of Spink (1999) and it was chosen to carry out semi-structured interviews as information production technique. For the analysis of the information, the speeches in dialogical maps were organized with the formation of analytical categories. The main results of the research pointed to the senses of humanization as a care technology focused on the doctor-patient relationship and in the ways in which the professional contexts make sense to the humanization learning in Medicine of the course in question. As intervention product, it was proposed the implementation of the Expanded Community of Research whose objective is to promote an intervention-training space based on the dialogue between the different workers and subjects of health production and on the encounter between the different knowledges.